Sequential Paired Electrochemical Transformation of Styrene Oxide via Anodic Meinwald Rearrangement and Cathodic Nitromethylation in an Electrochemical Flow Reactor with Catalytic Electrical Input - Sato, Eisuke; Nagamine, Kanon; Sasaki, Chika; Kunimoto, Shumpei; Mitsudo, Koichi; Suga, Seiji (Synthesis, 2024)
Paired electrosynthesis, which utilize both anodic and cathodic events in electrolysis, enables attractive transformations with higher current efficiency than conventional electrosynthesis. The electrochemical flow technique has been widely employed to ensure stable reaction conditions and mitigate issues stemming from mass transfer. In this study, the electrochemical Meinwald rearrangement of styrene oxides was investigated, yielding aldehydes as intermediates, followed by the nitromethylation of aldehydes to produce β-nitro alcohols. These reactions were achieved with catalytic electrical input, enabling the conversion of various styrene oxides into the corresponding β-nitro alcohols.
Keywords: electrochemical organic synthesis; paired electrolysis; Meinwald rearrangement; nitromethylation; flow synthesis